Research, action, activism: Critical solidarities & multi-scalar powers - Su, Celina (Education Policy Analysis Archives, 2019)
In this essay, I draw upon my work with the Urban Research Based Action Network (URBAN) to argue for several key principles in research for social justice: reflexivity, especially regarding our work in fraught academic institutions, and engaging multiple ways of knowing. These principles are essential to forming critical solidarities across constituencies, to recognizing and addressing issues of power at multiple scales—local, national, global, and to imagining ourselves as protagonists in our collective futures.